2014
DOI: 10.1523/jneurosci.0141-14.2014
|View full text |Cite
|
Sign up to set email alerts
|

RAGE Inhibition in Microglia Prevents Ischemia-Dependent Synaptic Dysfunction in an Amyloid-Enriched Environment

Abstract: Ischemia is known to increase the deleterious effect of ␤-amyloid (A␤), contributing to early cognitive impairment in Alzheimer's disease. Here, we investigated whether transient ischemia may function as a trigger for A␤-dependent synaptic impairment in the entorhinal cortex (EC), acting through specific cellular signaling. We found that synaptic depression induced by oxygen glucose deprivation (OGD) was enhanced in EC slices either in presence of synthetic oligomeric A␤ or in slices from mutant human amyloid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
43
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 83 publications
3
43
0
Order By: Relevance
“…This receptor is known to mediate the pro-inflammatory effect of Aβ, accelerating or amplifying the inflammatory response, leading to recruitment or activation of microglia and astrocytes [180]. Synaptic depression induced by oxygen glucose deprivation was enhanced by the presence of Aβ, and that depression was ameliorated when RAGE was inhibited [181]. As such, RAGE inhibition may be protective against the toxic effects of oxygen glucose deprivation, in an amyloid-enriched environment.…”
Section: Glial Dysfunction In Aging and Contribution To Neurodegeneramentioning
confidence: 99%
“…This receptor is known to mediate the pro-inflammatory effect of Aβ, accelerating or amplifying the inflammatory response, leading to recruitment or activation of microglia and astrocytes [180]. Synaptic depression induced by oxygen glucose deprivation was enhanced by the presence of Aβ, and that depression was ameliorated when RAGE was inhibited [181]. As such, RAGE inhibition may be protective against the toxic effects of oxygen glucose deprivation, in an amyloid-enriched environment.…”
Section: Glial Dysfunction In Aging and Contribution To Neurodegeneramentioning
confidence: 99%
“…Specifically, these studies have shown that the ablation of peripheral monocytes or RAGE/HMGB1 inhibition in peripheral monocytes, through genetic ablation of Ager or Hmgb1, provides benefits to mice with respect to hyperglycemiainduced impairments in stroke rehabilitation, including: decreased infarct area, prevention of BBB leakage, and decreased HMGB1 and RAGE expression, specifically in the cerebrum and microglia [85,86]. These findings were further supported by a subsequent study utilizing WT and AD-like mouse hippocampal slices subjected to oxygen glucose deprivation in the presence or absence of synthetic Aβ oligomers and showed that DN-RAGE targeted to the macrophage scavenger receptor promoter protected animals from ischemia and/or Aβ-induced synaptic impairments, thus implicating microglia RAGE in driving further detriments in ischemic cerebrovascular disease [87]. However, the previously mentioned caveats of DN-RAGE still pertain, and further mechanistic study of these findings utilizing more precise models would be helpful in elucidating the roles of central vs. peripheral myeloid cells and how other CNS cells, particularly ECs, are involved in RAGE-dependent cerebral ischemic impairments.…”
Section: Rage and Ischemic Cerebrovascular Disease: Acute And Chronicmentioning
confidence: 55%
“…The ERK pathway is activated by a number of receptors that bind Aβ, including the ionotropic and metabotropic glutamate receptors N-methyl-D-aspartate and mGluR5 [61][62][63][64][65], the receptor for advanced glycation end products [66,67], the p75 neurotrophin receptor, integrins, and a number of microglial receptors (reviewed in [68]). Aβ also interacts with alpha7 nicotinic receptors, which are required for Aβ-induced ERK and CREB phosphorylation [58].…”
Section: The Erk1/2 Mitogen-activated Protein Kinase Pathwaymentioning
confidence: 99%